Anterior Cervical Discectomy with or without Fusion in Non-traumatic Single level Cervical Disc Disorder: Study of 50 Cases (Journal of Dhaka Medical College, 2018)
Objectives: The aim of this study is to compare patients undergoing single level anterior cervical discectomy without fusion (ACD) versus anterior cervical discectomy with fusion (ACDF).Methods: A retrospective analysis of 50 patients with degenerative cervical spondylosis of them 25 had undergone ACD without fusion and remaining 25 undergone ACDF at either C4-C5, C5- C6 level or at C6-C7 level.Results: The kinematic analysis included the range of motion, intervertebral angulations, anteroposterior translation and disc height assessed for the cervical functional spinal units at the operated level and adjacent levels. At the operated level of C4-C5, C5-C6 and C6-C7, the range of motion and the translation were minimal in the anterior cervical discectomy without fusion (ACD) group, but absent in the cervical discectomy with fusion (ACDF) group. The superior adjacent levels range of motion and the translation were greater in the ACDF group compared with the ACD group. But both groups had almost similar results in term of hospital stay, mean time for improvement and patient satisfaction.Conclusion: The clinical results of anterior cervical discectomy without fusion (ACD) and anterior cervical discectomy with fusion (ACDF) were comparable. In cervical discectomy without fusion, the elastic fibrous intradiscal scar at the operated level allows a small degree of mobility and the adjacent cervical levels are not overstressed. Fusion is not routinely required in single level cervical disc herniation until it is associated with instability, loss of cervical lordosis, hard disc, osteophytic bar and multi-segmental disease. So ACD is a better option in single level cervical disc disorder than ACDF.J Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 29-35